2020
DOI: 10.1186/s13550-020-00673-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of the urokinase plasminogen activator receptor: opportunities beyond cancer

Abstract: The urokinase plasminogen activator receptor (uPAR) plays a multifaceted role in almost any process where migration of cells and tissue-remodeling is involved such as inflammation, but also in diseases as arthritis and cancer. Normally, uPAR is absent in healthy tissues. By its carefully orchestrated interaction with the protease urokinase plasminogen activator and its inhibitor (plasminogen activator inhibitor-1), uPAR localizes a cascade of proteolytic activities, enabling (patho)physiologic cell migration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 223 publications
(295 reference statements)
0
25
0
1
Order By: Relevance
“…This knowledge has been instrumental for designing a plethora of intervention strategies to target these components or their function with special emphasis on treatment modalities in oncology. Opportunities to target uPAR in inflammatory diseases beyond cancer should, however, also be considered ( Baart et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge has been instrumental for designing a plethora of intervention strategies to target these components or their function with special emphasis on treatment modalities in oncology. Opportunities to target uPAR in inflammatory diseases beyond cancer should, however, also be considered ( Baart et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…PLAUR encodes urokinase-type plasminogen activator receptor (uPAR) [ 136 ], which is a glycoprotein linked to the cell membrane by a glycosylphosphatidylinositol anchor [ 137 ]. The uPAR is a key regulator in many processes involving in not only cell signaling, proliferation, differentiation, and migration, but also tissue remodeling [ 137 139 ]. uPAR plays an important role in the early and injured brain.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in 1994, Bouhslav et al demonstrated that uPAR was a component of a large complex which included protein tyrosine-kinases and beta2 integrins expressed on the monocyte surface [ 29 ]. Since then, uPAR association with integrins, G protein-coupled receptors, receptor tyrosine-kinases (RTK) as epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor (PDGFR) and insulin-like growth factor 1 receptor (IGFR) has been shown, indicating uPAR as a central player in an extensive interactome including over 42 interacting proteins [ 30 ]; among them, uPAR interaction with integrins, G protein-coupled receptors and EGFR are definitely the most investigated and characterized.…”
Section: Upar Structure Interactors and Expressionmentioning
confidence: 99%
“…Increased uPAR expression may be observed in activated endothelium, smooth muscle cells and immune system cells, main players of inflammatory and immune responses [ 53 ]. Accordingly, up-regulation of uPAR expression is observed in the kidney during chronic proteinuric disease, in the central nervous system following ischemia or in neurodegenerative disorders such as Alzheimer’s disease and Creutzfeldt-Jakob disease, in atherosclerosis, in auto-immune diseases such as rheumatoid arthritis and systemic sclerosis, and in inflammatory bowel diseases consisting of chronic relapsing inflammatory disorders of the intestinal tract [ 30 , 54 ].…”
Section: Upar Structure Interactors and Expressionmentioning
confidence: 99%